The Analisis Of Islamic Value In Bedhaya Demak Dance - Setyaningrum, Ikha Sulis (Institut Agama Islam Negeri Palangka Raya, 2022)
Bedhaya is usually only found in Javanese palaces, bedhaya developed outside the palace is marked by the development of a more open type of bedhaya dance, meaning that bedhaya dances developed outside the palace are not always based on the existing bedhaya dance rules, one of which is the Bedhaya Tunggal Jiwa dance. The Bedhaya Tunggal Jiwa dance is packaged differently from the existing Bedhaya dance because it is adapted to the area and environment of the Demak community, so the formulation of the problem is as follows: How are the Islamic values contained in the creativity of the creation of the Bedhaya Tunggal Jiwa dance in Demak Regency. The purpose of this study is to describe and analyze Islamic values in the creativity of the creation of the Bedhaya Tunggal Jiwa dance by Dyah Purwani Setianingsih. The benefits of this research are divided into two, namely theoretical benefits and practical benefits. The research location chosen by the researcher is Pendhapa, Demak Regency. The method used is qualitative with an ethnochoreological approach, art anthropology, and art sociology. Data collection techniques include observation, interviews, and document studies. The technique of validating the data is using the source pol- ulation technique. Data analysis techniques were carried out by describing the dance, understanding the components of the performance, and interpreting it